Analysis of Enhanced OSPF for Routing Lightpaths in Optical Mesh Networks - Sengupta, Sudipta; Saha, D.; Chaudhuri, Surajit (IEEE International Conference on Communications (ICC) 2002, New York (USA), 2002)
We discuss enhancements to the OSPF (open shortest path first) protocol for routing and topology discovery in optical mesh networks. OSPF's opaque LSA (link state advertisement) mechanism is used to extend OSPF to disseminate optical resource related information through optical LSAs. Standard link-state database flooding mechanisms are used for distribution of optical LSAs. Each optical LSA carries optical resource information pertaining to a single optical link bundle between two adjacent OXCs (optical cross connects), allowing for fine granularity changes in topology to be incorporated in path computation algorithms. OSPF packets are carried over a single IP control channel between adjacent OXCs. We analyze the performance of OSPF with optical extensions. Specifically, we compute control channel bandwidth used due to LSA updates. We also estimate the amount of memory required to store the LSA database. Finally, we study CPU usage for computing primary and backup lightpaths. Our analysis shows that the control channel bandwidth usage, memory requirement, and CPU usage are small enough to not be limiting factors for designing optical networks with single OSPF areas consisting of a large number (more than 500) of OXCs.